2009
DOI: 10.1021/ma901237h
|View full text |Cite
|
Sign up to set email alerts
|

PLGA−POSS End-Linked Networks with Tailored Degradation and Shape Memory Behavior

Abstract: Biodegradable PLGA oligomers were synthesized to feature a hybrid organic-inorganic moiety, POSS, incorporated at the center of each chain by using it as the ring-opening initiator. After end-capping with vinyl groups, the macromers were photocured into networks with POSS content ranging from 10 to 41 wt %. Increasing POSS inclusion increased the crystallinity of the network while decreasing the degradation rate due to its hydrophobic and nonhydrolyzable properties. It was found that co-curing PLGA oligomers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…The degradation rate can be determined by varying POSS content; a higher POSS content corresponds to a slower degradation rates. 27 Together with the mechanical integrity, the degradation rate of the POSS-PCL-PU films can be controlled to achieve a scaffold that degrades slowly during the initial period, followed by rapid degradation at the later phase after the growth of the cells. This behavior is desired because the scaffold's structural integrity is required in the initial phase for cells to attach and proliferate.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation rate can be determined by varying POSS content; a higher POSS content corresponds to a slower degradation rates. 27 Together with the mechanical integrity, the degradation rate of the POSS-PCL-PU films can be controlled to achieve a scaffold that degrades slowly during the initial period, followed by rapid degradation at the later phase after the growth of the cells. This behavior is desired because the scaffold's structural integrity is required in the initial phase for cells to attach and proliferate.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of poly(TMC) also affected the crystallization of poly(LA), as expected. 14,24 The GrPLC1 curve shows an undetectable peak for T m , even in the first heating run. The results demonstrate that the incorporation of TMC units changes the crystallinity of the graft chains containing LA units.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Poly(TMC) has been reported to have a lower T g , of less than À20 1C. 24 Consequently, the observed T g s are thought to show those of the grafted LA polymer. The peak observed at ca À15 1C seems to be the T g of the grafted poly(TMC) in the case of GrPCL2.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Several studies have assessed the influence of POSS moieties on the degradation of polymeric biomaterials. Knight et al [17] investigated the in vitro degradation of PLA-based polyurethanes with 20.8 wt.% POSS incorporation and found a slower rate of degradation compared with the non-POSS material after eight weeks exposure in a PBS buffer at 37 C. More recently, Knight et al [16] studied the effect of POSS content on the degradation profile of poly(lactide-co-glycolide) (PLGA) containing 10e41 wt.% POSS. The authors observed that by increasing the POSS content in the system the rate of degradation decreased.…”
Section: Mass Loss Studymentioning
confidence: 99%